2021
DOI: 10.1097/shk.0000000000001899
|View full text |Cite
|
Sign up to set email alerts
|

ETS-Related Gene Activation Preserves Adherens Junctions and Permeability in Microvascular Endothelial Cells

Abstract: ERG (ETS-related gene) is a member of the ETS (Erythroblast-transformation specific) family of transcription factors abundantly present in vascular endothelial cells. Recent studies demonstrate that ERG has important roles in blood vessel stability and angiogenesis. However, it is unclear how ERG is potentially involved in microvascular barrier functions and permeability. A wide variety of diseases and clinical conditions including trauma-hemorrhagic shock and burn injury are associated with microvascular dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…A probable mechanism for the disappearance of reactive local hyperthermia in the fingertips of the patients studied with blood loss may be the development of microvascular endothelial dysfunction [ 27 , 28 ]. Endothelial cells are known to regulate vasoreactivity and vascular permeability through the synthesis of nitric oxide, a powerful vasodilator [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A probable mechanism for the disappearance of reactive local hyperthermia in the fingertips of the patients studied with blood loss may be the development of microvascular endothelial dysfunction [ 27 , 28 ]. Endothelial cells are known to regulate vasoreactivity and vascular permeability through the synthesis of nitric oxide, a powerful vasodilator [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Numerous studies have reported on ERG's regulatory roles in cell growth, proliferation, differentiation, and apoptosis. 5,6 Studies have confirmed the association between ERG expression and the development of different cancers. In prostate cancer cells, for instance, the fusion of the ERG and TMPRSS2 genes can facilitate cancer cell proliferation, invasion, angiogenesis, invasiveness, and activate downstream oncogenes, 7,8 thereby enhancing their transcriptional activity.…”
Section: Introductionmentioning
confidence: 91%
“…Erythroblast transformation‐specific‐related gene ( ERG ), a member of ETS transcription factor family, is a transcription factor that is widely expressed and can be induced by various growth and differentiation stimulators in many cell types 4 . Numerous studies have reported on ERG's regulatory roles in cell growth, proliferation, differentiation, and apoptosis 5,6 . Studies have confirmed the association between ERG expression and the development of different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite limited evidence regarding histone modification, DNA methylation, and histone deacetylase activity in BMECs, recent studies [90,91] have demonstrated that dysregulation of microRNAs and long non-coding RNAs disrupts the integrity of the BBB. Specifically, the dysregulation of miR124, miR-107, and LINC00662 alters the transcription of ZO-1, claudin-5, and occludin in BMECs of AD patients through the modification of members belonging to the erythroid transformation-specific (ETS) transcription factor family and ETS-related genes [92].…”
Section: The Specific Mechanism Of Bbb Affecting Ad Progression 41 En...mentioning
confidence: 99%